2009
DOI: 10.1007/s10875-009-9276-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased IgG Antibody-Induced Cytotoxicity Against Airway Epithelial Cells in Patients with Nonallergic Asthma

Abstract: Background IgG autoantibodies to airway epithelial cell proteins have been detected in patients with nonallergic asthma. Objective and Methods To evaluate the functional significance of these autoantibodies, we examined the presence of IgG antibody-induced cytotoxicity against airway epithelial cells (A549) by the microcytotoxicity assay using IgG antibodies purified from patients with nonallergic asthma. Results IgG antibody-induced cytotoxicity (expressed as percent cell lysis) was significantly increased in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 28 publications
1
10
0
1
Order By: Relevance
“…Several environmental allergens sharing structural similarities with human proteins can be autoantigens 14-16. Some tissue antigens were thought to be derived from thyroid proteins and epithelial cells interacting with environmental factors 9,10,17. This study5 also confirmed the presence of human IgE antibodies reacting to thyroglobulin, which is closely associated with the autoimmunity of chronic urticaria 11.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Several environmental allergens sharing structural similarities with human proteins can be autoantigens 14-16. Some tissue antigens were thought to be derived from thyroid proteins and epithelial cells interacting with environmental factors 9,10,17. This study5 also confirmed the presence of human IgE antibodies reacting to thyroglobulin, which is closely associated with the autoimmunity of chronic urticaria 11.…”
supporting
confidence: 66%
“…Several studies have suggested that autoimmune mechanisms play an important part in the development and progression of chronic allergic inflammation in subsets of asthma,9,10 chronic urticaria,11 and atopic dermatitis patients 12. Moreover, the chronic urticaria patients with high specific IgE to thyroid peroxidase showed a favorable response to anti-IgE therapy 13.…”
mentioning
confidence: 99%
“…Autoreactive immune mechanisms induced either by molecular mimicry or as a consequence of chronic allergic inflammation and the generation of cytotoxic autoantibodies have been described (33). IgG antibodies directed against epithelial proteins, such as cytokeratin-18, have been detected in adults with intrinsic asthma (33) where dysregulated epithelial repair and impaired resolution of the inflammation might also play a role.…”
Section: Intrinsic (Nonatopic) Asthmamentioning
confidence: 99%
“…Circulating antibodies to cytokeratin‐18 and α‐enolase, which occur in epithelial cells, have been described in patients with intrinsic asthma and more severe asthma (61, 62). IgG autoantibodies from patients with intrinsic asthma have cytotoxic effects on epithelial cells, whereas these antibodies are not found in extrinsic asthma (63). It is possible that these autoantibodies damage airway epithelial cells so that superantigen‐producing organisms are able to more easily infect the airway surface.…”
Section: Non‐atopic Allergic Diseasementioning
confidence: 99%